Dual modality ultrasound - photoacoustic clinical imaging system and its applications - Sivasubramanian, Kathyayini (2018)
Photoacoustic (PA) imaging is a rapidly growing hybrid biomedical imaging modality. Translating it to the clinic still remains a challenge which needs to be addressed. Using a clinical ultrasound imaging system if one can do dual modal ultrasound as well as photoacoustic imaging, it will be a big step towards clinical translation. Such system will provide the flexibility of combining with a variety of lasers and transducers to image various different body parts. By combining it with a high repetition rate pulsed laser diode, high frame rate PA imaging can be achieved. The high frame rate imaging is highly useful for real-time photoacoustic imaging. Energy from pulsed laser diode is low, and not all applications require high frame rate imaging. Therefore, a frequency doubled Nd:YAG laser pumping an optical parametric oscillator was also combined with the clinical ultrasound system for handheld dual modal ultrasound and photoacoustic imaging. A bifurcated optical fiber used for light illumination was integrated with the ultrasound probe. The imaging angle, the distance between fiber and tissue etc. was optimized using Monte Carlo simulations to finalize the handheld imaging probe holder design. The handheld probe was used for two different pre-clinical applications: sentinel lymph node imaging, and urinary bladder imaging. Firstly, sentinel lymph nodes in rats was imaged with methylene blue (675 nm) and indocyanine green (795 nm) as contrast agent. Non-invasive, real time needle tracking was also performed. Imaging depth similar to human imaging scenario was demonstrated. Furthermore, combined ultrasound and PA imaging of rat urinary bladder was demonstrated with the handheld probe. Structural and functional bladder imaging was shown. Also, the feasibility of PA imaging for a common bladder disorder, vesicoureteral reflux was studied using urinary tract mimicking phantoms. Additionally, non-invasive clearance study of gold nanorods from circulation was done by monitoring the accumulation of the gold nanorods in the bladder. Contrast agents are very important for improving photoacoustic signal strength and having multiple FDA approved contrast agent will make clinical translation more feasible. Two different contrast agents were explored in this work. With the development of combined dual modal imaging, dual modal contrast agents are needed. A dual modal organic dyes containing nitrogen microbubbles (<7 μm) generated from a flow focusing junction based microfluidic device. Here, the organic dyes (methylene blue and black ink) will provide the photoacoustic contrast and the nitrogen microbubbles will offer the ultrasound contrast. The efficiency of the contrast agent was initially tested in tube phantoms and later in in vivo studies. Another contrast agent explored is a potential theranostics agent, near-infrared light-sensitive liposomes coated with gold nanostars (AuNSs) for both PA imaging and drug release. We explored the use of AuNSs-coated liposomes as contrast agents for PA imaging with tissue phantom experiments.